(untitled) (Research, Society and Development, 2020)
Drinks composed of more than one fruit are a trend in the national and international market, presenting advantages such as greater nutritional value and the development of new flavors. So, the objective was to elaborate six formulations of mixed nectar of mango and passion fruit, varying the percentage of each pulp and soluble solids content, as well as evaluating its physicochemical, microbiological, sensorial and stability properties. The nectars were prepared by the hot fill process and packed in 500 ml glass bottles, and then submitted to the analyzes. The nectars presented pH between 2.86±0.05 and 3.33±0.15, soluble solids of 10.00 to 14.83 ºBrix, acidity of 0.59 to 0.78g acid citric/100g nectar, and vitamin C from 15.36 to 33.66 mg/100g. The microbiological analyzes presented values according to the current legislation. The formulations were within the sensory acceptance zone for the tasters, with a balance in the evaluated attributes. F4 (10g of passion fruit and 20g of mango) was chosen among the formulations due to greater acceptance and use of a lower percentage of passion fruit, reducing the cost of the product. In relation to the stability, none of the sensorial attributes presented differences in the interval of 150 days, however, for the physical-chemical attributes, it was observed difference in pH, total acidity, vitamin C and total soluble solids. Therefore, it is necessary to better assess the physical and chemical characteristics, with the intention of increasing the nutritional index of the product.